Analisis Pengendalian Kualitas Green Beans Kopi Menggunakan Metode Statistical Process Control (SPC) di Kopi Bontugu Trawas - Kevlin Adelia; Sri Tjondro Winarno; Ika Sari Tondang (SAFE-Network, 2026)
The quality of coffee green beans is one of the important factors that determine the quality of coffee products. However, in the production process, various types of defects are still found that can reduce the quality and selling value of the product. This study aims to analyze the quality control of Arabica coffee green beans at Kopi Bontugu Trawas, Mojokerto Regency using the Statistical Process Control (SPC) method. The study was conducted using a quantitative descriptive approach with primary data. Data analysis was carried out using check sheets, Pareto diagrams, control charts (p-chart), and fishbone diagrams. The results showed that out of a total production of 319,500 grams, 33,489 grams were defective, consisting of broken beans, beans with holes, black beans, wrinkled beans, and moldy beans. The Pareto diagram shows that broken bean defects are the dominant issue, contributing 51.5%, followed by hole defects at 38.7%, so these two types of defects make up 90.2% of total defects. The control chart results show that the production process is not yet statistically controlled because there are six points outside the control limits. The fishbone analysis indicates that broken bean defects are influenced by material, machine, and method factors. Improvement efforts that can be done include harvesting ripe coffee cherries, regular maintenance and adjustment of the huller machine, and controlling the drying process and moisture content of the coffee beans. This study shows that applying SPC can help identify the sources of defects and serve as a basis for improving green bean coffee quality.